Frederic Eugene Ives and Herbert Eugene Ives papers - Ives, Frederic Eugene, 1856-1937.; Ives, Herbert Eugene, 1882-1953.
Correspondence, journals, speeches, writings, notebooks, patents and patent applications, biographical material, subject files, clippings, scrapbooks, and other papers relating to the inventions of Frederic Eugene Ives and Herbert Eugene Ives. Inventions include improved photographic methods and equipment, such as aerial and color photography, phototelegraphy, and other devices and techniques which were precursors of commercial television. Correspondence includes a discussion of Albert Einstein's theories. Correspondents include, E.E. Butterfield, George Eastman, Albert Einstein, George V, King of Great Britain, Courtney H. Hodges, and Harry S. Truman, and members of the Ives family.
Frederic Eugene Ives, inventor and photographer; and his son, Herbert Eugene Ives, physicist and television pioneer.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Butterfield, E. E. -- Correspondence; Eastman, George, -- 1854-1932 -- Correspondence; Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955 -- Correspondence; George -- V, -- King of Great Britain, -- 1865-1936 -- Correspondence; Hodges, Courtney H., -- 1887-1966 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Ives family -- Correspondence; Aerial photography; Color photography; Photography; Phototelegraphy; Physics; Television; Inventors; Photographers